Semiotics in John Edmond’s “The Last Word in Rhodesian” Song - Gani, Firmansyah; Herlyna, Herlyna; Marleni, Sri (e-Journal of Linguistics; Vol 18 No 2 (2024): ejl-JulyDO - 10.24843/e-jl.2024.v18.i02.p15, 2024)
The exploration of literature transcends the boundaries of written texts, encompassing a diverse array of expressions, including spoken or sung compositions like song lyrics. While on the surface, songs may seem to convey straightforward messages, beneath it lies a labyrinth of symbols and nuances that beckon listeners to interpret. This interpretive process demands a nuanced understanding and a willingness to explore the depths of lyrical expression. This research aims to unravel the significance of each letter in the word "RHODESIA" and to unravel the intricate composition of the portmanteau "Rhodesian" within the lyrics of John Edmond's ‘The Last Word in Rhodesian’ song using Ferdinand de Saussure's dyadic model of semiosis and employing qualitative research methodology with historical approach. Through meticulous analysis, the findings reveal the profound symbolism interwoven within the lyrics, which serves to encapsulate the historical essence of Rhodesia. The songwriter adeptly utilizes the arrangement of each letter in the word "RHODESIA" to encapsulate phrases emblematic of the Rhodesian Bush War and alluding to the names of significant Rhodesian figures; Rhodes and Ian, symbolically forming the word “Rhodesian”. In doing so, the song becomes a poignant tribute to the complex tapestry of Rhodesian history.